Qualidade de cebola minimamente processada em diferentes tipos de cortes - Antunes, Andréa Maria [UNESP]; Manoel, Luciana [UNESP]; Evangelista, Regina Marta [UNESP]; Ono, Elizabeth Orika [UNESP]; Vieites, Rogério Lopes [UNESP] (Assoc Brasileira Horticultura, 2014)
The high perishability of the onion has limited its conservation period and caused great post-harvest losses. The need of consuming fresh products has led the market of minimally processed products to considerably rise. Cut operations during the minimal processing may not only cause important biochemical reactions in the onion tissues, but also affect its sensorial quality, resulting in a drastic reduction in the post-harvest life of the product. In this study the influence of different cut types was assessed on the quality of minimally processed onions. 'Baia Periforme'onions were transported to the laboratory, where they were selected, cleaned, classified, peeled, minimally processed into slices, grated and chopped, and subsequently sanitized for 10 minutes in sodium hypochlorite at 100 mg L-1. The product was kept on polystyrene trays covered with plastic film (PVC) as 80 g portions and conserved in a cold chamber at 5 +/- 1 degrees C and 85 +/- 5% RH, during 6 days. Physical, chemical and physico-chemical assays were carried out. Statistical design was completely randomized with 3 treatments and 3 replications (plot group) and 5 replicationss for the control group. For sensorial analysis (aspect and smell), 10 replications were used. To compare means, Tukey test at 5% significance was adopted. During the refrigerated conservation, sliced onions kept more stable levels of soluble solids, titratable acidity, total sugars, reducing and non-reducing sugars. The grated onion was superior considering the sensorial characteristics, indicating that the cut types interfered in these features and the grated onion was more accepted by evaluators.

A alta perecibilidade da cebola tem limitado seu período de conservação e proporcionado altas perdas pós-colheita. A necessidade em se consumir produtos frescos tem levado o mercado de produtos minimamente processados a um grande aumento. Operações de corte durante o processamento mínimo podem não apenas causar importantes reações bioquímicas nos tecidos da cebola como também afetar sua qualidade sensorial, resultando numa redução da vida pós-colheita do produto. O objetivo deste trabalho foi avaliar a influência de diferentes cortes sobre a qualidade de cebolas minimamente processadas. Cebolas cv. Baia Periforme foram transportadas para o laboratório onde foram selecionadas, limpas, classificadas, descascadas, minimamente processadas em rodelas, raladas e picadas, posteriormente, sanitizadas por 10 minutos em hipoclorito de sódio a 100 mg L-1. O produto foi mantido em bandejas de isopor recobertas com filme de PVC em porções de 80 g e conservadas em câmara fria a 5±1º C e 85±5% de UR, durante 6 dias. Foram realizadas avaliações físicas, químicas e físico-químicas. O delineamento estatístico utilizado foi inteiramente casualizado com 3 tratamentos e 3 repetições (grupo parcela) e 5 repetições para grupo controle. Na análise sensorial (aparência e aroma) utilizaram-se 10 repetições. Para a comparação entre as médias foi utilizado o teste Tukey a 5% de probabilidade. As cebolas fatiadas em rodelas mantiveram mais estáveis os teores de sólidos solúveis, acidez titulável, açúcares totais, açúcares redutores e não redutores durante a conservação refrigerada A cebola ralada, destacou-se em relação às características sensoriais, indicando que os tipos de cortes interferiram nestas características e que a cebola processada ralada foi a mais aceita pelos avaliadores.
Quality of fresh-cut onion subjected to different cut types
Keywords: Allium cepa; Conservation; Processing; Shelf life; Allium cepa; Conservação; Processamento; Vida de prateleira